(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The lightwell is an architectural solution to promote daylight into the internal spaces from the core of a building. The shaft configurations, such as geometry and reflectance can affect the performance of the daylighting entering the adjoining rooms under different conditions. This study aims to indicate the adequate architectural solutions to improve the daylighting performance of buildings with lightwells at three different southern latitudes. From a base model of 6-stories building, alternative cases were parametrically simulated using Rhinoceros, GrassHopper and ClimateStudio software. From variations in the lightwell geometry and walls reflectance, the cases were analyzed considering the lighting metrics UDI and sDA300. Results demonstrate that the daylighting is adequate on the floors near the top of the building and weakens towards the base of it. In Macapá, São Paulo and Chile, the sDA values reach 100 % on the top floor, but only 3 % on the first floor. It was also observed that materials with high diffuse reflectance on the shaft is more efficient in improving the daylighting performance than increasing its geometry. This research presents early-design guidance to inform architects and policymakers when considering the exploitation of daylight by the use of the lightwell.